EPAC-lung: pooled analysis of circulating tumour cells in advanced non-small cell lung cancer. (August 2019) - Lindsay, C.R.; Blackhall, F.H.; Carmel, A.; Fernandez-Gutierrez, F.; Gazzaniga, P.; Groen, H.J.M.; Hiltermann, T.J.N.; Krebs, M.G.; Loges, S.; López-López, R.; Muinelo-Romay, L.; Pantel, K.; et al.
Abstract: Introduction: We assessed the clinical validity of circulating tumour cell (CTC) quantification for prognostication of patients with advanced non-small cell lung cancer (NSCLC) by undertaking a pooled analysis of individual patient data. Methods: Nine European NSCLC CTC centres were asked to provide reported/unreported pseudo-anonymised data for patients with advanced NSCLC who participated in CellSearch CTC studies from January 2003 to March 2017. We used Cox regression models, stratified by centres, to establish the association between CTC count and survival. We assessed the added value of CTCs to prognostic clinicopathological models using likelihood ratio (LR) statistics and c-indices. Results: Seven out of nine eligible centres provided data for 550 patients with prognostic information for overall survival. CTC counts of ≥2 and ≥ 5 per 7·5 mL were associated with reduced progression-free survival (≥2 CTCs: hazard ratio [HR] = 1.72, p < 0·001; ≥5 CTCs: HR = 2.21, p < 0·001) and overall survival (≥2 CTCs: HR = 2·18, p < 0·001; ≥5 CTCs: HR = 2·75, p < 0·001), respectively. Survival prediction was significantly improved by addition of baseline CTC count to LR clinicopathological models (log-transformed CTCs p < 0·001; ≥2 CTCs p < 0·001; ≥5 CTCs p ≤ 0·001 for both survival end-points), whereas moderate improvements were observed with the use of c-index models. There was some evidence of between-centre heterogeneity, especially when examining continuous counts of CTCs. Conclusions: These data confirm CTCs as an independent prognostic indicator of progression-free survival and overall survival in advanced NSCLC and also reveal some evidence of between-centre heterogeneity. CTC count improves prognostication when added to full clinicopathological predictive models. Highlights: This European pooled analysis of circulating tumour cells (CTCs) in non-small cell lung cancer (NSCLC) is the largest study of its kind. It is the first to examine between-centre heterogeneity of CTC identification. CTCs are an independent prognostic marker in advanced NSCLC. There is no difference in CTC profile between key NSCLC molecular subsets.